Do general radiographic examinations resemble a person-centred environment?. Issue 4 (November 2016) - Hayre, C.M.; Blackman, S.; Eyden, A.
Abstract: Aim and objective: It is argued whether general radiographic examinations adhere to a person-centred approach within the direct digital radiography (DDR) environment. General radiographic examinations continue to increase and constitute approximately 90% of all examinations undertaken in the clinical environment. This study explored the potential impact patients experience whilst undergoing general imaging examinations. Method: An ethnographic methodology provided insight of two general radiography environments in the United Kingdom (UK) using participant observation and semi-structured interviews. Findings: The findings highlighted an 'in and out' culture whereby patients are 'hurried' and 'rushed' out of X-ray rooms in response to increasing time pressures experienced by diagnostic radiographers. In addition, this study challenged that patients may begin to rank 'speed' and 'waiting times' above other elements of radiographic care thus presenting new challenges for radiographers within the clinical environment. Conclusion: It is asserted that radiographers should remain holistic healthcare professionals and not begin to resemble operators on the production line. Further, it challenges whether patients are beginning to rank aspects of radiographic care within contemporary practices. Advances in knowledge: Few studies have explored the radiographer–patient relationship within the DDR environment, yet this study provides insight of person-centred practices within contemporary practices. Highlights: Challenges whether the use of DDR conforms to a person-centred approach. Challenges whether radiographers are 'treating patients as persons' using DDR. Patients may begin to rank 'speed' and 'waiting times' above other aspects of radiographic care.